Pancréatite aiguë médicamenteuse: à propos de 10 cas - Maghrebi, Houcine (Pan Afr Med J, 2017)
Drug-induced acute pancreatitis (AP) accounts for approximately 2% of acute pancreatitis. Its incidence is increasing, with more than 260 incriminated drugs. However, very few cases have been described in the literature due to accountability problem. We report our experience with 10 cases whose data were collected over a period of 7 years. Clinical presentation of AP was often equivocal. Ranson’s score ranged from 0 to 5. We recorded 5 cases of edematous pancreatitis and 5 cases of necro-bleeding pancreatitis. These pancreatitis were often successfully treated without recurrence after discontinuation of the incriminated drug.